Assessment of Serum Levels of the Matrix-Metalloproteinase-9, Prostaglandin E-2 and Cyclo-Oxygenase-2 as a Candidate Biomarker of Chronic Obstructive Pulmonary Disease (COPD) - Adnan Riaz, Ahmad Ashar Ghuman, Sabeen Khalid, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic obstructive pulmonary diseases are one of the crucial and increasing global health complications. It has highest prevalence not only in Pakistan but also the large cases of COPD are reported world widely. Objective: The study was carried out to find the relationship between elevated serum level of Prostaglandin E2, Matrix-metalloproteinase-9 and Cyclo-oxygenase-2 and Chronic obstructive pulmonary diseases. Study design: It is a case control study conducted at department of biochemistry, Islam Medical College, Sialkot for the duration of six months from February 2022 to July 222. Material and Methods: The patients suffering from chronic obstructive pulmonary disease were selected for the study. Two groups were made, control group contained 41 healthy individuals and diseased group contained 39 patients. All the patients that were not according to the inclusion criteria were excluded from the study. Results: Average age of patients was calculated and it came out to be 57 years in case of control group and 61 for COPD patients. There were almost similar numbers of male and female members in both groups. The body mass index was also calculated and it was found that 15 participants from the COPD group fell under 23-25 kg/m2 group. Conclusion: The level was found to be high for Matrix-metalloproteinase-9, Prostaglandin E-2 and Cyclooxygenase- 2 in the serum of patients suffering from COPD. The level was increasing as the GOLD grading was increased. Smoking is positively related to the severity of chronic obstructive pulmonary diseases. The level of, PGE-2 and COX-2 showed a positive association with the chronic obstructive pulmonary diseases patients. Keywords: biomarker and Chronic obstructive pulmonary diseases.